Strain Rate and Temperature Effects of the JOXL‐1 Explosive. Issue 9 (8th July 2022) - Zhu, Xintao; Zhang, Xiaojing; Li, Wenbin; Yao, Wenjin
Abstract: To determine the influence of temperature and strain rate on the mechanical behavior of JOXL‐1 explosive, the stress‐strain curves of JOXL‐1 explosive at different temperatures (233 K‐473 K) and different strain rates (110 s −1 ‐400 s −1 ) were measured using a split Hopkinson pressure bar (SHPB) experimental system with a temperature control device. The results show that the dynamic mechanical properties of this explosive are sensitive to the strain rate and temperature in the experimental temperature range. The failure stress increases with increasing strain rate and decreases with increasing temperature. The failure strain increases with increasing strain rate, but it is almost unaffected by temperature. The DSC analysis shows that the JOXL‐1 explosive has good thermal stability when the temperature is lower than 391.37 K and that binders in the explosive gradually decompose when the temperature is higher than 391.37 K. Abstract :